Living with severe perinatal depression: a qualitative study of the experiences of labour migrant and refugee women on the Thai-Myanmar border - Fellmeth, Gracia (BMC Psychiatry, 2018)
BACKGROUND: Perinatal depression is an important contributor to maternal morbidity and mortality worldwide. Migrant women, particularly those resettling within low- and middle-income settings, are at increased risk of perinatal depression due to multiple stressors experienced before, during and after migration. Evidence on migrant perinatal mental health to date has focused largely on women in high-income destination countries, leaving the voices of displaced women in low-income settings unheard. This study addresses the current evidence gap by exploring the experiences of migrant women living on the Thai-Myanmar border. METHODS: In-depth interviews were conducted with pregnant and post-partum labour migrant and refugee women on the Thai-Myanmar border who had been diagnosed with severe depression. An interview guide covering women’s current and past life experiences, social support and the impact of depression on social and occupational functioning was used as a prompt. Thematic analysis was used to identify themes emerging from women’s narratives. RESULTS: Eleven pregnant and post-partum women with severe perinatal depression took part. Participating women provided extensive insight into the many difficult aspects of their lives that they perceived as contributing to their depression status. Predominant themes emerging from women’s narratives included difficult relationships with partners, challenging life situations, mechanisms for coping with depression and impressions of mental health care. CONCLUSIONS: Labour migrant and refugee women with severe perinatal depression face a wide range of chronic stressors at the individual, household and community levels that are likely to have both short- and long-term negative effects on their mental well-being and day-to-day functioning. Participating women responded positively to the mental health support they received, and findings provide important insights into how services might further support their needs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12888-018-1815-7) contains supplementary material, which is available to authorized users.